Optical physics for nanolithography - Yen, Anthony; Yu, Shinn-Sheng (SPIE Press monograph, 2018)
This book provides an in-depth, self-contained introduction of partially coherent imaging theory for researchers and engineers working on optical lithography for semiconductor manufacturing, including those in the EDA industry. It is mathematically complete: the opening chapters discuss the essential principles, and all derivations are presented with their intermediate steps. For increased accessibility, simplified and consistent notations are used throughout the text. Full-color pages illustrate the connections between figures and equations.